KONSEP KELUARGA SAKINAH MENURUT KEMENTRIAN AGAMA TERHADAP KELUARGA JAMA’AH TABLIG - Putra, Adi; Siagian, Nilasari; Ameliyah, Siti (UIN Sumatera Utara Medan, 2023)
Between husband and wife and children and other family members respect each other and understand each other's rights and obligations, so that sakinah is created in household life, especially among the Jama'ah Tabligh family, Departing from the fact that the teachings adopted by Jama'ah Tabligh teach its followers to carry out khuruj or preach by leaving their families at home which then not a few families experience failure in building a sakinah family. The process and meaning (subject perspective) are more emphasized in qualitative research. The theoretical basis is used as a guide so that the focus of the research is in accordance with the facts in the field. In the masturoh activity they learn and deepen their knowledge about how to be a pious wife, a good mother, how to educate their children and communicate with the community and others. The conclusion of this study is that the researcher concludes that a sakinah family according to the Tablighi Jama'ah is a harmonious and peaceful family concept, where family members support each other in religious and moral activities and maintain peace and tranquility in the household